Inflammation Associates With Impaired Small Arterial Elasticity Early in HIV Disease. (19th May 2018) - Peterson, Tess E; Huppler Hullsiek, Katherine; Wyman Engen, Nicole; Kumarasamy, Nagalingeswaran; Lebech, Anne-Mette; Liappis, Angelike; Papadopoulos, Antonios; Polizzotto, Mark N; Schreiner, Pamela J; Duprez, Daniel; Baker, Jason V; ,
Abstract: We estimated small arterial elasticity and used linear regression to evaluate its association with inflammatory biomarkers among antiretroviral therapy–naïve, HIV-positive patients with high CD4+ counts. After adjustment, high-sensitivity C-reactive protein and interleukin-6 were inversely associated with small arterial elasticity. These data suggest that systemic inflammation may contribute to vascular dysfunction even in very early HIV disease.